Saltwater Chronicles: Reading Representational Spaces in Selected Book Clubs in St. John's, Newfoundland - Judith P. Robertson; David Lewkowich; Jennifer Rottmann (Island Studies Journal, 2010)
_Saltwater Chronicles_ investigates the notion of “islandness” in contemporary Newfoundland readership through two in-depth case studies of book clubs as representational spaces in the elaboration of local knowledge and identities. We demonstrate how select Newfoundland readers perform acts of regeneration in which the lived, loved, and experiential dimensions of literary space come to invoke the permeability of psychic and geographic borders, the dangers and possibilities of the landwash, and the always-already precarious designation of limits between self and other. We provide examples of how, for these island readers, “islandness” as a symbolic point of address slips and border-crosses in the in-between semiotic spaces of literary encounter.